The Analysis of TPACK’s Ability to Increase the Professionalism of Elementary School Teachers in DKI Jakarta - Muhammad Hayun; Maesaroh Lubis; R.Andi Ahmad Gunadi; Masroro Diah Lestari (AL-ISHLAH: Jurnal Pendidikan, 2023)
The study aims to analyze the Technological Competence, Pedagogics, and Content Knowledge (TPCK) of elementary school teachers and how to integrate and implement TPACK in learning. The research method used is descriptive quantitative survey research with the population and sample being elementary school teachers in DKI Jakarta, which are taken randomly using a simple random sampling technique. Data collection instrument used the TPACK Self-assessment instrument developed by researchers. The results of this study are: the use ICT in learning by elementary school teachers in DKI Jakarta has not been maximized, low skills of technology cause this; Online learning platforms, both synchronous and asynchronous, are still monotonous; not many choices are used, even direct to be conventional;  The use of learning applications that help in the presentation of subject matter is still deficient and monotonous.